Scientific Research and Scientific Performance Evaluation - Cumhur Ertekin (Türk Nöroloji Dergisi, 2014)
Scientometric measures were reviewed for the scientific papers of scientists (citations, H-index.. so on) and the measurement were also made for the scientific periodics and the institutes of scientific research. Scientometric values were compared to the related output of our country. Unfortunately we have reached a conclusion that our scientific research should have more efforts to approach to the level of the general scientific world.